PREVALENCE OF OBESITY AND ASSOCIATION WITH OTHER CARDIOVASCULAR RISK FACTORS IN A GROUP OF YOUNG MEDICINE STUDENTS - Adriana, Gherbon (European Scientific Journal, ESJ, 2013)
Background&Aims: Obesity, especially abdominal type, is one of the modifiable cardiovascular risk factors which present an increasing prevalence in children and adolescents. The purpose of this study is to assess the prevalence of overweight and obesity in young students from the Faculty of Medicine of Timisoara, in the first and second year of study, and to determine if there is a relationship between obesity and cardiovascular risk factors (family history, smoking, physical inactivity and hypertension). Methods: The studied group was represented by 518 students (375 girls and 143 boys) aged 20 ± 2 years. Were used clinical, biochemical and imaging parameters. Results: 4.26 ± 1.23% of girls and 15.38 ± 2.33% of the boys had a BMI between 25 and 29.9 kg/m2 and 0.55% ± 0.1% of girls and 4.19 ± 1.13% of the boys had a BMI between 30 and 39.9 kg/m2. 67.3 ± 15% had an unhealthy diet (increased consumption of fats and refined carbohydrates) associated with physical inactivity in proportion of 28.8 ± 8.66% and stress in proportion of 53 ± 17%. 82 ± 25% of subjects showed besides obesity, at least two associated cardiovascular risk factors. We note also the decrease of HDL - cholesterol < 50 mg% at 5 ± 1.23% of girls and < 40 mg% at 25 ± 9.6% of boys. Conclusions: Obesity and overweight was predominant at boys; there was an increased incidence of cardiovascular risk factors related to lifestyle, which requires a series of cardiovascular prevention measures since young age.